Desenvolvimento de modelos para flavonoides e cumarinas utilizando o campo de força CGenFF - Souza, Carolina Penhavel de [UNESP] (2014)
The use of computational simulations as a tool in the study of biomolecular systems creates the possibility to observe the behavior, organization and interaction of the components at atomic/molecular level. Among several computational simulation techniques, the most used is Molecular Dynamics (MD). MD plays an important role in structure determination, dynamics and function of molecular systems due to the simplicity of its potential function. This and their respective parameterization are generically known as force fields. Among the existing force fields, CHARMM is one of the most used and improved today. In order to model molecules of pharmaceutical interest that interact with biomolecules, an extension of this force field, the CHARMM General Force Field (CGenFF), was developed. The construction of the initial version of the CgenFF was based in molecules which compose CHARMM, such as phenol, parameterized as a precursor for tyrosine. All the parameters already available in the CHARMM are converted and combined to produce new types of atoms. Nevertheless, the CGenFF should be used only for pharmacological molecules; the biological molecules should be represented by the original CHARMM force field. The study of molecules of pharmacological interest from natural sources (vegetable, animal or mineral) always resulted in the development of drugs highly efficient to fight several diseases. Approximately 50% of the drugs introduced on the market, during the last 20 years, are derived from small biogenic molecules. Among the natural components with great potential for use as drugs we can highlight flavonoids, our study object: they are polyphenolic compounds naturally present in vegetables, fruit, seeds, nuts and drinks like tea and red wine. These molecules are derived from benzo-γ-pirone and present a wide range of biological activity (antiallergenic, anti-inflammatory, antioxidant, antiviral and...